Approches sur l’historiographie du genre à Byzance - Georges Sidéris (Genre & Histoire)
Gender Studies hold an important place in Byzantine Studies. Roles of women and eunuchs as well as masculinity and male domination in the Byzantine society are now well recognized. Gender studies in Byzantium do reflect the diversity and the specificity of this society.